The idea of sustainable development as the idea of harmonious development - Tomanek, Roman (Studia Ecologiae et Bioethicae, 2018)
Sustainable development, both the term itself and social activities which the term denotes, is related to various areas of environmental protection. The term is defined in different ways depending on the area in which it is applied. With fairly strict definitions of sustainable development to be found in science, government documents, international agreements, and the economy, the word is often used as a fashionable slogan or a trivial label in everyday life situations. The purpose of this article is to analyze both the term and the idea of sustainable development, as well as the epistemic status of the concept, in order to capture its essential meaning. Two Kantian categories are applied in this analysis: a regulative idea and a practical postulate. The use of these categories makes it possible to relate the analysis to the idea of harmony. Consequently, it is argued that the idea of sustainable development is in fact the idea of harmonious development.